Bacterial and Fungal Adaptations in Cecum and Distal Colon of Piglets Fed With Dairy-Based Milk Formula in Comparison With Human Milk - Elolimy, Ahmed; Rosa, Fernanda; Tripp, Patricia; Zeineldin, Mohamed; Bowlin, Anne K.; Randolph, Christopher; Robeson, Michael S.; Yeruva, Laxmi (Frontiers in Microbiology, 2022)
Exclusive breastfeeding is recommended to newborns during the first 6 months of life, while dairy-based infant formula is an alternative nutrition source offered to infants. Several studies demonstrated that breastfed infants have a different gut bacterial composition relative to formula fed infants. Additionally, animal models have shown that human-milk fed had a distinct intestinal bacterial composition compared to milk-formula fed. However, the gut fungal composition and the interactions with the bacterial community in breastfed compared to formula fed infants remains to be investigated. In an attempt to evaluate such differences, we used an animal model to perform a shotgun metagenomics analysis on the cecal and distal colon contents of piglets fed pasteurized human milk (HM) or a dairy-based infant formula (MF) during the first 21 days of life. At postnatal day 21 (PND 21), a subset of piglets from each diet group (n = 11/group) were euthanized. The remaining piglets in each group were weaned to a solid diet and euthanized at PND 51 (n = 13/group). Large intestine contents (i.e., cecum and distal colon) were subjected to shotgun metagenomics analysis. The differential taxonomic composition of bacteria and fungi as well as the predicted functional gene profiling were evaluated. Bacteroidetes, Firmicutes, Proteobacteria, and Actinobacteria are the most abundant bacterial phyla observed in piglets at PND 21 and PND 51. In the large intestine at PND 21 and PND 51 Proteobacteria phylum was significantly higher in MF fed group and species Burkholderiales bacterium of phyla was significantly higher in MF group relative to HM group. In addition, in HM group several Lactobacillus spp. and Bacteroides spp. were higher relative to MF group in the large intestine at PND 21 and PND 51. Fungal genus Aspergillus was higher in MF while Malassezia was lower relative to HM group. Persistent effects of the neonatal diets were observed at PND 51, where alpha- and beta-diversity differences were detected for bacterial and fungal species in the large intestine. Overall, data indicate that neonatal diet affects the large intestinal microbial community during the exclusive milk-feeding period, as well as after the introduction of the complementary food.